Effect of intercropping with herbaceous legumes on the yield and quality of Napier grass in the central highlands of Kenya - Mwangi, David Miano; Giller, Kenneth E.; Thorpe, W.R.; Thomas, D. (British Society of Animal Science, 1998)
Dairy production in an important enterprise for many smallholders in the East African highlands, where population pressure is high and inheritance traditionally leads to the subdivision of land holdings. As a result, farm sizes are decreasing such that in Kiambu District, central Kenya, they average only 0.8 ha (Staal et al., 1997). Dairy is based mainly on the cut-and-carry (zero-grazing) system in which Napier grass (Pennisetum purpureum) is the dominant fodder, complemented by crop residues (principally from maize) and roadside grasses. Generally farmers preferentially fertilise cash and food crops, not Napier grass, the yields of which are therefore low. The limited supply of fodder, when combined with the same quantities of purchased concentrates, results in average daily milk yields of 6-8 litres from high grade dairy cows (Omore et al., 1996; Staal et al., 1997). As a step towards developing higher yielding forage systems to support increased milk production, Napier grass was intercropped with three herbaceous legumes and harvested at different heights and frequencies to study the effects on forage yield and quality.